Կնոջ կերպարը Հմայակ Հակոբյանի արվեստում - Պետրոսյան, Արմինե (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Образ женщины занимает особое место в творчестве тифлисского армянского художника-представителя академической школы живописи Амаяка Акопяна (1871–1939). Посредством женских образов художник выразил свои чувства, мысли, свое душевное состояние. Созданные им портреты и зарисовки представляют собой общий, собирательный образ женщины его эпохи. Для творчества мастера характерны реалистичность и лиричность. Тема эстетики обнаженного тела широко представлена в живописи и графике художника. The image of a woman takes a special place in the work of the Tiflis Armenian artist, representative of the academic school of painting Hmayak Hakobyan (1871–1939). Through female images, the artist expressed his feelings, thoughts, and his state of mind. The portraits and sketches he created represent a generalized, collective image of a woman of his era. Realism and lyricism are characteristic of the master's work. The theme of aesthetics of the naked body is widely represented in the artist's paintings and graphics.
Keywords: Արվեստագիտություն